Superficial parotidectomy versus extracapsular dissection: literature review and search for a gold standard technique. Issue 2 (February 2020) - Martin, H.; Jayasinghe, J.; Lowe, T.
Abstract: Benign parotid tumours usually present as a slow-growing, asymptomatic mass in the pre-auricular region. Although they are uncommon, surgical excision is the mainstay of treatment due to the risk of malignant transformation in some benign tumours. Surgical techniques have evolved over the years, with superficial parotidectomy and extracapsular dissection being the current procedures of choice. There is currently no gold standard, and it remains unclear which surgical modality is the superior option. A literature review was performed in relation to the relative merits of each technique and to evaluate the reasons underpinning the ongoing debate. A total of 16 papers comparing the main clinical outcomes of the procedures were critically reviewed using the PRISMA protocol. Overall, extracapsular dissection indicated a reduced recurrence rate, facial nerve paralysis, Frey syndrome, and operation time. The superior outcomes following extracapsular dissection could be attributed to the less radical nature of the procedure. However, there were various limitations identified within the review that may have affected the results. Selection bias was the most significant, with patients assigned to the different procedures depending on the tumour size and location. Consequently, the debate continues as to what constitutes the gold standard of care for benign parotid tumours.